Motivation across a transition: Changes in achievement goal orientations and academic well-being from elementary to secondary school - Heta Tuominen; Markku Niemivirta; Kirsti Lonka; Katariina Salmela-Aro (Elsevier, 2025)
The aim of this study was to examine i) the prevalence of achievement goal orientation profiles among Finnish sixth- and seventh-graders (N = 419), ii) the stability and change in these profiles across the transition from elementary to lower secondary school, and iii) the profile differences in academic achievement (grades) and academic well-being (school engagement and school burnout). Using latent profile analysis, four goal orientation profiles were extracted: indifferent, success-oriented, mastery-oriented, and avoidance-oriented. Latent transition analysis confirmed that these profiles were stably identified over time. There was substantial stability in profiles: being assigned to the same group yielded the highest transition probabilities (0.63–0.75). Likely transitions were from success-oriented to indifferent and from indifferent to avoidance-oriented. Of those who transitioned, the majority moved from more to less favorable profiles. Students who stayed in the mastery-oriented group across the transition displayed the most adaptive pattern of motivation, academic achievement, and well-being.